2020
DOI: 10.1590/0104-1428.01020
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and analysis of melamine and melamine-silica as clarifying agents of waste lubricating oil

Abstract: Melamine is a key compound used as a clarifying agent for waste lubricating oil primarily due to its excellent adsorbent properties. Moreover, considerable interest exists for the further modification of melamine in order to provide a remediation agent with improved clarification capacity. In this study, hexamethylolmelamine was prepared using a solution of formaldehyde, which provided an agent capable of incorporation into a silicate polymer framework. Subsequently, the resultant monomer was added to a soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Calculations revealed that the average crystallite size of these particles is about 13–15 nm. The lack of the characteristic peaks of melamine in the X-ray diffraction pattern of the as prepared foam along with the wide shoulder at about 25° confirm the reaction of melamine with formaldehyde and the formation of amorphous melamine–formaldehyde resin in the as prepared foam 33 36 . Decomposition of Zn(NO 3 ) 2 to ZnO particles, by the following chemical reaction, can be accompanied by the formation of carbon foam 32 , 37 :
Figure 1 Structural development of the synthesized foam during thermal treatment ( a ) X-ray diffraction patterns of the synthesized foams, ( b ) Thermal gravimetric analysis results of the prepared foams with 2, 4 and 6 g of Zn(NO 3 ) 2 .6H 2 O, ( c ) Raman Spectra of the carbon foams.
…”
Section: Resultsmentioning
confidence: 78%
“…Calculations revealed that the average crystallite size of these particles is about 13–15 nm. The lack of the characteristic peaks of melamine in the X-ray diffraction pattern of the as prepared foam along with the wide shoulder at about 25° confirm the reaction of melamine with formaldehyde and the formation of amorphous melamine–formaldehyde resin in the as prepared foam 33 36 . Decomposition of Zn(NO 3 ) 2 to ZnO particles, by the following chemical reaction, can be accompanied by the formation of carbon foam 32 , 37 :
Figure 1 Structural development of the synthesized foam during thermal treatment ( a ) X-ray diffraction patterns of the synthesized foams, ( b ) Thermal gravimetric analysis results of the prepared foams with 2, 4 and 6 g of Zn(NO 3 ) 2 .6H 2 O, ( c ) Raman Spectra of the carbon foams.
…”
Section: Resultsmentioning
confidence: 78%
“…Besides, the peak of N–H sp 2 of melamine at 3418 cm −1 disappeared, while two new peaks were observed at 3325 and 3126 cm −1 and could be ascribed to N–H sp 2 and N–H sp 3 of melamine. 38…”
Section: Resultsmentioning
confidence: 99%
“…The diffractogram shows two peaks at 26.35 and 39.5 that correspond to the two characteristic peaks of melamine with a little shi was observed in the position of the former peaks and disappearance of the other peaks, and this conrmed that melamine had participated in the synthesis of the obtained MOF. 38 The peaks at 2q; 17.21 , 25.07 , and 29.57 that represent the terephthalic acid peaks showed a small deviation from the characteristic peaks of pure terephthalic acid. 49 Further three peaks were detected at 13.62 , 27.67 , and 31.76 which could be considered as characteristic peaks of strontium chloride hexahydrate with a small shi from its ideal peaks' positions.…”
Section: Mtsr-mof-nps Characterizationmentioning
confidence: 94%
See 2 more Smart Citations